The Paris wife [compact disc, unabridged] : a novel - McLain, Paula (Random House, Inc., 2011)
In this fictional memoir, Hadley Hemingway chronicles the life and career of her husband, famed twentieth century writer Ernest Hemingway. Through Hadley's unique perspective, listeners get a behind-the-scenes look into the personal lives of the Lost Generation writers, including Scott Fitzgerald, Gertrude Stein, and Ezra Pound.